Applicability of a human cell co-culture model to evaluate antioxidant responses triggered by chemical mixtures in fish and oyster homogenates. (June 2019) - Sutherland, Grace E.; Franco, Marco E.; Willing, Sarah M.; Lavado, Ramon
Abstract: The accumulation of chemical compounds in fish tissue represents significant health concerns for seafood consumers, but little is known about the risks to human health associated with such substances. The identification of adverse biological responses upon exposure to contaminants has been facilitated by the development of in vitro systems resembling the human dietary pathway. The present study explores the applicability of an organotypic co-culture system, using intestinal (Caco-2) and hepatic (HepaRG) cell lines, to provide insight into the toxicity of chemical mixtures found in commercially available seafood. Chemical extractions were conducted utilizing fish and oyster standard reference material (SRM) from the U.S. National Institute of Standards and Technology (NIST). Cells were seeded in monoculture and co-culture systems and exposed to SRM extracts before measurements of cytotoxicity and antioxidant responses. Exposure to oyster extracts led to significant cell mortality in monocultures. HepaRG cells in monoculture expressed lower levels of glutathione peroxidase and superoxide dismutase than HepaRG cells in co-culture, upon exposure to both oyster and fish extracts. These observations illustrate the importance of organotypic co-culture models to explore biological responses that could be otherwise difficult to evaluate in monocultures, and the adverse effects associated with the consumption of contaminated seafood. Graphical abstract: Image 1 Highlights: The intestinal and hepatic cell co-culture system proves advantageous for assessing antioxidant responses. Exposure to homogenate extracts led to significantly high cell mortality in monocultures compared to organotypic cultures. Hepatocytes in monoculture showed lower levels of antioxidant enzyme activity than in co-culture. Contrasting results between cell culture methods highlight the need to appropriately select cell-based bioassays.